2015
DOI: 10.1111/avsc.12161
|View full text |Cite
|
Sign up to set email alerts
|

Ecological disturbance regimes caused by agricultural land uses and their effects on tropical forest regeneration

Abstract: Aims: Across tropical regions, large forest areas have been converted to different agricultural land uses. These uses impose ecological disturbances affecting forest regeneration potential after field abandonment. Finding ways to identify those agricultural land uses limiting forest regeneration is a critical issue for conserving biodiversity in human-modified landscapes. Here, we developed a fast and inexpensive index, useful for quantifying ecological disturbance regimes associated with agricultural land use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 58 publications
1
77
0
8
Order By: Relevance
“…After major disturbances where the removal of vegetation was complete, or nearly so [71], it has been recognized that early stages of succession post disturbance are characterized by dominance of pioneer species such as grasses, shrubs, and other short-lived species [72,73]. Therefore, besides the evidently disturbed bare-soil areas, we include the low and dense herbaceous vegetation in the disturbance category as early transition stages for Scrub vegetation, because the abandonment of cultivars, grasslands and other disturbed areas is related to recovery of the vegetation [74]. In this regard, evidence shows that abandonment of cultivated areas and pasture fields results in the development of thorny vegetation [75], this being one of the communities considered within the Scrub vegetation in our study.…”
Section: Successional Stages Of the Main Types Of Vegetation In The Nmentioning
confidence: 99%
“…After major disturbances where the removal of vegetation was complete, or nearly so [71], it has been recognized that early stages of succession post disturbance are characterized by dominance of pioneer species such as grasses, shrubs, and other short-lived species [72,73]. Therefore, besides the evidently disturbed bare-soil areas, we include the low and dense herbaceous vegetation in the disturbance category as early transition stages for Scrub vegetation, because the abandonment of cultivars, grasslands and other disturbed areas is related to recovery of the vegetation [74]. In this regard, evidence shows that abandonment of cultivated areas and pasture fields results in the development of thorny vegetation [75], this being one of the communities considered within the Scrub vegetation in our study.…”
Section: Successional Stages Of the Main Types Of Vegetation In The Nmentioning
confidence: 99%
“…We characterized the livestock management regimes using a set of indicators using an ad hoc approach drawing from the growing literature on ecological, agronomic and socio-ecological assessments of ecosystem management (Alkemade et al, 2013;Van Oudenhoven, 2015;Zermeño-Hernández et al, 2015). The land use is pasture for livestock production and the land management involves planting alien grasses, slashing and burning for pasture maintenance, and managing livestock by modifying stocking density and grazing periods, which together comprise the components of these management regimes.…”
Section: Characterization Of the Management Regimes And Its Componentsmentioning
confidence: 99%
“…From a social-ecological perspective (Reyers et al, 2013), management regimes are also dependent on the biophysical and social conditions within which the different management practices are undertaken (Van Oudenhoven, 2015). While a range of management regime indicators (Alkemade et al, 2013;Zermeño-Hernández et al, 2015) have been derived from the intersection of these approaches, and the range of ecosystem service indicators is growing (Layke et al, 2012;Van Oudenhoven et al, 2012), the impact of alternative management regimes and their components on ecosystem services needs to be further assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In the tropics, however, there is a wide array of agricultural land uses, and their impact on forest regeneration potential, once a field is abandoned, is poorly known (Melo et al, 2013;Zermeño-Hernández et al, 2015). In this context, a first step for exploring agriculture land uses which are friendly to biodiversity conservation is to quantify the diversity of agricultural land uses in the landscape, assess the ecological disturbance regimes imposed by such uses, and evaluate the impact of these disturbance regimes on forest regeneration potential (Zermeño-Hernández et al, 2015). Because in recent times there has been a global trend of land abandonment in the tropics (Cramer et al, 2008;Aide et al, 2013), this issue is of wide relevance.…”
Section: Introductionmentioning
confidence: 99%
“…We based this analysis on an ecological disturbance index (EDI) we developed elsewhere with information provided by farmers and landowners (Zermeño-Hernández et al, 2015). We have shown that EDI is an inexpensive, quickly and efficiently predictor of forest regeneration potential at the field scale; we proved that plant density, richness, and species diversity of regenerating forest trees decrease exponentially as EDI increases.…”
Section: Introductionmentioning
confidence: 99%